A new application of multistage homotopy perturbation method to the chaotic Rössler system - Chowdhury, Md. Sazzad Hossien; Razali, Nur Isnida; Ali, Sellami; Rahman, Md. Mahmudur (American Institute of Physics, 2012)
In this paper, we present a numerical scheme based on an adaptation of the standard homotopy-perturbation method (HPM) is applied to the Chaotic Rössler system. The standard HPM is converted into a hybrid numeric-analytic method called the multistage HPM (MHPM). Comparisons with the fourth-order Runge-Kutta method (RK4) and standard HPM show that the MHPM is a reliable method for nonlinear equations.